2016
DOI: 10.1007/s11060-016-2076-2
|View full text |Cite
|
Sign up to set email alerts
|

Pro-apoptotic and anti-angiogenic properties of the α /β-thujone fraction from Thuja occidentalis on glioblastoma cells

Abstract: The most aggressive type of brain tumor is glioblastoma multiforme, which to date remains incurable. Thuja occidentalis is used in homeopathy for the treatment of cancer, however, its mechanism of action remains unknown. We set out to study the effects of thujone fractions of Thuja on glioblastoma using in vitro and in vivo models. We found that the α/ β-thujone fraction decrease the cell viability and exhibit a potent anti-proliferative, pro-apoptotic and anti-angiogenic effects in vitro. In vivo assays showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 45 publications
4
31
0
1
Order By: Relevance
“…and pulegone in O. vulgare . In agreement with our results in Artemisia judaica oil (mainly composed of thujone), Torres et al [ 59 ] reported that the thujone enriched fraction has potential anticancer activities. The use of capillin (1–10 uM), isolated from A. monosperama , inhibited cell proliferation of HT29, MIA PaCa-2 and HEp-2 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…and pulegone in O. vulgare . In agreement with our results in Artemisia judaica oil (mainly composed of thujone), Torres et al [ 59 ] reported that the thujone enriched fraction has potential anticancer activities. The use of capillin (1–10 uM), isolated from A. monosperama , inhibited cell proliferation of HT29, MIA PaCa-2 and HEp-2 [ 32 ].…”
Section: Discussionsupporting
confidence: 93%
“…In this same work, the in vivo effect of thujone fractions in a subcutaneous allograft rat model was evaluated. Similar to the results obtained in vitro, the α/β thujone fraction promoted tumor regression without generating adverse effects in the treated animals and also decreased expression of the angiogenic markers VEGF, Angiopoietin 4 (Ang‐4), and CD31 into the tumor (Torres et al, ).…”
Section: Terpenessupporting
confidence: 62%
“…Thuja occidentalis crude extract is widely used in alternative medicine for the treatment of several diseases, including neoplasms (Torres et al, ). This extract of T .…”
Section: Terpenesmentioning
confidence: 99%
“…Recently, Küpeli Akkol et al (2015) revealed the anti-carcinogenic potential of a-thujone. This compound inhibited the proliferation of glioblastoma cells and angiogenesis, and in a rat model it stimulated an anticancer immune response (Torres et al 2016). Immuno-modulatory properties of thujone have been determined by Siveen and Kuttan (2011a) on both humoral and cell mediated immune systems as well as on solid tumor development.…”
Section: Biological Activities and New Ways For Beneficial Utilizatiomentioning
confidence: 99%
“…Essential oil of T. occidentalis containing thujone as a major compound, has been widely used in folk medicine for the treatment of hepatoprotection, bronchial catarrh, rheumatism, psoriasis, and uterine carcinomas (Küpeli Akkol et al 2015;Dhiman et al 2012). In homeopathy, the extract of T. occidentalis containing about 65% a-thujone, is used as mother tincture in preparations against a number of diseases (Torres et al 2016). Thuja preparations with thujone were regularly used by the American Indian traditional healers.…”
Section: Biological Activities and New Ways For Beneficial Utilizatiomentioning
confidence: 99%